Effect of valence holes on swift heavy ion track formation in Al2O3 - Terekhin, Pavel (2015)
This paper focuses on effects of electrons and valence holes on structure modifications in swift heavy ion (SHI) tracks in dielectrics. To investigate this problem a multiscale model is constructed which consists of (a) Monte Carlo modeling of a SHI penetration and secondary electron cascading; (b) molecular-kinetic approach for low-energy electrons spatial redistribution after finishing of ionization cascades; (c) molecular dynamics modeling of lattice excitation due to its coupling with the relaxing electron ensemble and subsequent atomic dynamics on picoseconds timescales. The model is applied to 167 MeV Xe ion irradiation of solid Al2O3. We found that lattice heating by excited electrons does not exceed ∼200 K, which is not sufficient to form an ion track observed in experiments. Structure transformations appear in the numerical simulations only when the excess energy accumulated in valence holes is taken into account.